Coloniality, extractivism and resistance in the Peruvian Amazon - Bernuy Arenas, Susan Carol (2021)
The territories of what is now Latin America and the Caribbean went through violent colonisation processes, which installed power structures at the political, economic, social and cultural levels, all and generated deeply asymmetrical relationships. Years later, with processes of independence, abolitionist and the formation of nation-states, instead of eliminating these power structures, they were camouflaged and transformed into strategies, discourses and practices that have continued to reproduce the colonial logic. The aim of this essay is to analyse how coloniality continues to exist through extractivism and how, in the face of its impacts, indigenous peoples carry out processes of resistance in defence of territory and life. Methodologically, a bibliographical and documentary analysis of the theoretical and conceptual proposals on coloniality and extractivism from Latin American and Caribbean critical thinking and of the case of oil pollution in lot 192 (ex 1AB) and lot 8, located in the north of the Peruvian Amazon, was carried out. Based on this analysis, final reflections are shared.